1995
DOI: 10.1101/gad.9.15.1857
|View full text |Cite
|
Sign up to set email alerts
|

Biallelic expression of imprinted genes in the mouse germ line: implications for erasure, establishment, and mechanisms of genomic imprinting.

Abstract: Genomic imprinting in mammals determines parental-specific (monoallelic) expression of a relatively small number of genes during development. Imprinting must logically be imparted in the germ line, where inherited maternal and paternal imprinting is erased and new imprinting established according to the individual's sex. We have assessed the allele-specific expression of four imprinted genes, two of which exhibit maternal-speeitic (H19 and Ig/2r} and two of which exhibit paternal-specific (lg/2 and Snrpn) mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
133
0
2

Year Published

1996
1996
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(142 citation statements)
references
References 72 publications
7
133
0
2
Order By: Relevance
“…The expression pattern of the hum an IG F2R gene at earlier stages of development is still unknown. In the mouse, both maternal and paternal Ig f2 r alleles are expressed during preimplantation development (Latham et al, 1994;Szabo and Mann, 1995), indicating that in this species, monoallelic expression is due to secondary in activation of one Ig f2 r gene copy. Along these lines, biallelic expression of the hum an IG F2R gene might result from failing repression of the paternal allele.…”
Section: Cpg 1 Is Completely Unmethylated On Both Parental Igf2r Allementioning
confidence: 99%
“…The expression pattern of the hum an IG F2R gene at earlier stages of development is still unknown. In the mouse, both maternal and paternal Ig f2 r alleles are expressed during preimplantation development (Latham et al, 1994;Szabo and Mann, 1995), indicating that in this species, monoallelic expression is due to secondary in activation of one Ig f2 r gene copy. Along these lines, biallelic expression of the hum an IG F2R gene might result from failing repression of the paternal allele.…”
Section: Cpg 1 Is Completely Unmethylated On Both Parental Igf2r Allementioning
confidence: 99%
“…A 10-g aliquot of total RNA was loaded per lane. Allele-specific expression was determined using reverse transcription-PCR single-nucleotide primer extension assays as described previously (40,41). Each assay relies on a single known sequence difference between allelic RNAs.…”
Section: Methodsmentioning
confidence: 99%
“…Males homozygous for the mutant ICR (Ϫ/Ϫ) were mated to normal CF1 females (Charles River), and the resulting adult ϩ/Ϫ females were superovulated (11). Oocyte collection was done as published previously (40). Four separate bisulfite reactions were done on pools of 190, 150, 175, and 175 oocytes embedded into agarose beads (25), and each reaction was PCR amplified separately.…”
Section: Dna Methylation Of the Icr In Germ Cells (I) Perinatal Germmentioning
confidence: 99%
“…Differential methylation of cytosine residues in CpG dinucleotides in critical regions of imprinted genes is part of the imprinting process differentiating paternal and maternal alleles (Barlow, 1993). Imprinted genes have been well analysed in terms of genome reprogramming, and it is widely accepted that imprinting memories are erased in PGCs and that DNA methylation is an important factor in this process (Grant et al, 1992;Kafri et al, 1992;Brandeis et al, 1993;Szabo and Mann, 1995b;Kato et al, 1999). Maternally expressed H19 is one of the best-characterized imprinted genes.…”
Section: Introductionmentioning
confidence: 99%
“…Takai et al (2001) have shown that only the sixth of the seven CTCF-binding sites demonstrates allele-specific methylation. Expression of imprinted genes, such as H19, in the germ line become biallelic at day 11.5 of mouse embryonic development (Szabo and Mann, 1995b;Villar et al, 1995). Loss of allele-specific methylation imprints has also been observed in both male and female PGCs of the mouse (Tada et al, 1998).…”
Section: Introductionmentioning
confidence: 99%